2005
DOI: 10.1016/j.jacc.2004.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Progenitor Cell Activity in Age-Related Endothelial Dysfunction

Abstract: Maintenance of vascular homeostasis by EPCs may be attenuated with age based on functional deficits rather than depletion of CD34/KDR or CD133/KDR cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
352
0
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 516 publications
(387 citation statements)
references
References 39 publications
24
352
0
11
Order By: Relevance
“…Their findings are similar to ours for PCs; however, we used a more stringent definition of EPCs that included the VEGF-R2 receptor. Another study, however, showed no differences in the numbers of circulating EPCs, defined as CD34/VEGF-R2 or CD133/VEGF-R2 double-positive cells in peripheral blood but there was lower survival, migration, and proliferation implicating functional impairment of EPCs from older subjects (19).…”
Section: Discussionmentioning
confidence: 93%
“…Their findings are similar to ours for PCs; however, we used a more stringent definition of EPCs that included the VEGF-R2 receptor. Another study, however, showed no differences in the numbers of circulating EPCs, defined as CD34/VEGF-R2 or CD133/VEGF-R2 double-positive cells in peripheral blood but there was lower survival, migration, and proliferation implicating functional impairment of EPCs from older subjects (19).…”
Section: Discussionmentioning
confidence: 93%
“…Deficiency in function and number of EPCs is associated with endothelial dysfunction (Scheubel et al, 2003;Heiss et al, 2005;Tao et al, 2006;Hoetzer et al, 2007). The data reported here showed that endothelial function measured by flow-mediated vasodilation in the brachial artery as well as in vitro SDF-1-induced migration and TNF-astimulated adhesion to HUVECs was markedly impaired in elderly men compared with young men, similar with prior reports (Taddei et al, 1995;Tao et al, 2004;Heiss et al, 2005;Hoetzer et al, 2007). Moreover, reendothelialization capacity of in vivo EPCs derived from elderly men was significantly reduced in a nude mouse carotid artery injury model.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional cardiovascular risk factors are diverse and include smoking, aging (29), hypercholesterolemia, hypertension, hyperglycemia (30), and a family history of premature atherosclerotic disease. All of those risk factors are associated with attenuation͞ loss of endothelium-dependent vasodilation.…”
Section: Effects Of Flavanol-rich Foods On Vascular Function and No Smentioning
confidence: 99%